Caught in the Air: Symptomatic Cerebral Arterial Air Embolism during Endovascular Flow Diversion - Chidanandaswamy, Naveen; Vyas, Sameer; Bhagat, Hemant; Karthigeyan, Madhivanan (Indian Journal of Radiology and Imaging, 2025)
Symptomatic cerebral arterial air embolism (CAAE) is a rare complication of endovascular procedures. Early diagnosis and management are critical to alleviate neurological deficits and to prevent mortality. Neurointerventionists should take prompt action on suspicion of air embolism to prevent catastrophic consequences. Hyperbaric oxygen therapy is the treatment of choice, however, in its nonavailability, multiple measures can be taken immediately to minimize complications and to promote dissolution of air emboli. We report a case of CAAE during endovascular treatment of unruptured left ophthalmic internal carotid artery aneurysm using a flow diverter, which was actively managed with a good outcome.
Keywords: air embolism; cerebral arterial air embolism; endovascular flow diversion